Forage Consumption and Its Effects on the Performance of Growing Swine—Discussed in Relation to European Wild Boar (Sus scrofa L.) in Semi-Extensive Systems: A Review - M. Jordana Rivero; Vicente Rodríguez-Estévez; Silvana Pietrosemoli; Cecilia Carballo; Andrew S. Cooke; Anne Grete Kongsted (Animals, 2019)
Due to its distinct properties, wild boar meat is considered a highly desirable consumer product, in a market that is expanding. Outdoor production is also favoured by consumers who value animal welfare and environmental sustainability when choosing meat products. There is evidence that farms that include pasture for grazing typically have reduced feeding costs. Such production systems can also be more environmentally sustainable as the input (pasture) is inedible to humans, compared to conventional indoor systems, which use human-edible feeds (e.g., soya). However, some wild boar farms have performed poorly compared to those rearing other swine such as hybrid wild boar and domestic pigs. Diet is central to all livestock production and is likely a significant influencing factor of wild boar performance, both in terms of forage consumption and nutritional composition. Other factors may also influence performance, such as weather, behaviour and grazing management. Wild boar production systems hold their own intrinsic value in a growing marketplace. However, information gathered through the study of wild boar has external applications in informing outdoor domestic pig production systems to encourage the use of pasture as part of the habitat of domestic pigs.